(untitled) (Sociologisk Forskning, 2010)
Toughness for a soft society? On medialisation, racialisation and the politics of spin in Sweden In recent years, issues concerning the future of “multicultural Sweden” have become a salient feature in Swedish politics. One important actor in recent years’ debates about the problems confronting “multicultural Sweden” is the Swedish Liberal Party. Since the general election of 2002, the party has gained both publicity and electoral support by focusing the question of “integration of immigrants” in terms of assimilation and intensified demands aimed at the “immigrant Others”. In this article, the party’s recent developments in the area of integration policy is analysed within the framework of two general processes in contemporary politics, the politics of racialisation and the medialisation of politics. The party’s successful interventions in the area of integration policy are built on an intimate as well as complex interplay between racialisation and medialisation. The agenda articulated by the party, further, has several similarities with the agenda of “authoritarian populist” movements throughout Europe.